Enhancing Teachers' Capacity in Flood Disaster Mitigation Education in Schools to Foster Disaster-Prepared Schools": Peningkatan Kapasitas Guru dalam Edukasi Mitigasi Bencana Banjir di Sekolah untuk Mewujudkan Sekolah Siaga Bencana - Hatibu, Hardiyanti; Zahra Mulianti Natsir, Sitti; Handayani L, Rifhani; Usman, Hikmawati; Nur Abdullah, Muhammad (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service activity aims to enhance the capacity of elementary school teachers in delivering flood disaster mitigation education as a strategic effort toward the realization of Disaster-Prepared Schools (Sekolah Siaga Bencana). The activity was carried out at SD Negeri Aroeppala in Makassar City, involving 29 teachers as training participants. The implementation employed a one-group pre-test and post-test approach to measure the increase in participants’ knowledge following the educational intervention. The training materials covered fundamental concepts of flooding, contributing factors, impacts, and relevant mitigation strategies in the school environment. The evaluation results indicated an increase in the average score from 62.41 to 84.48, with a significance value of 0.01 (< 0.05), suggesting a statistically significant improvement in knowledge. The enthusiasm and active participation of the participants demonstrate that the training was effective and aligned with the needs of teachers in disaster-prone areas. This program is recommended for replication in other schools as an effort to strengthen a culture of disaster awareness in primary education settings.